Marketing Strategy of High Throughput Satellite (HTS) Utilization For Indonesian Multifunctional Services in 3t Area - Florian Falah, Tembang (Journal of Economics and Business UBS, 2023)
Indonesia, as the biggest archipelagic country in the world, has a problem with the distribution of its network infrastructure to provide broadband access across the regions. It is very important to provide broadband access because Indonesia has entered the digital era which needs to access the data, Indonesia’s capacity needs to access the data are growing rapidly. A submarine cable can provided to connect the connections between cities and provinces, especially in the 3T area (frontier, outermost, and least developed region), but there’s still a lot of area in Indonesia that can’t covered with fiber optic cable because of many factors, the company can complete the uncovered area with satellite, named High Throughput Satellite (HTS) that will be completed in 2023. Based on condition above, the company must immediately develop an business strategy after the HTS activity, considering the business competition in Telecommunication industry. This study will be develop an marketing strategy for PT Angkasa Satu. The analysis used in preparing the alternative strategy in based on observations of internal and external factors of the company. The strategy analysis is carried out using the quantitative strategic planning matrix (QSPM) method, TOWS analysis and the IE Matrix. The EFE and IFE Matrix are used to analyse the company’s strength, weaknesses, opportunities and threats. Then TOWS analysis will define the several alternative strategy based on EFE and IFE. All the alternative will be calculated using the IE Matrix and QSPM. The result of this thesis is the strategy of focusing on the HTS external market utilization (marketing strategy) and the relevant strategy applied by the company to face the competition in the future.